The Constitutional Law Implications and Polemics of Extending the Village Head's Term of Office: A Critical Analysis - Anang Dony Irawan; Ida Ayu Rosida; Ega Permatadani (Pancasila and Law Review)
Village administration is pivotal to national economic development and resilience, a role formally recognized with the enactment of Law Number 6 of 2014 concerning Villages. Prior to this legislation, the recognition of village governance was primarily based on Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This article investigates the mechanisms for community participation in the amendment of laws and regulations concerning villages and scrutinizes the controversy over extending the village head’s term of office from the perspective of Indonesian constitutional law. Utilizing a normative juridical approach combined with statute and library research methods, this research involves the systematic collection, review, and analysis of relevant data and sources. This research aims to contribute to the understanding of village governance within Indonesia’s democratic framework, contrasting it with the more authoritarian systems seen in communist regimes, and highlights the implications of the Village Law on village authority and the tenure of village heads.